The Sleeping Giant Awakes: Projecting Global Implications of China's Energy Consumption - Zhang, Jian (2012)
China's rapid economic growth has generated a surge in energy demand that is reallocating global fuel balances. We employ a global energy computable general-equilibrium model to analyze alternative scenarios for economic growth, Chinese currency appreciation, and oil price shocks, with a special focus on China energy markets. Imports from the Middle East, Central Asia, Russia, and Sub-Saharan Africa are found to comprise a growing share of China's energy. Imports to China grow from 12% of world energy imports in 2010 to 17% by 2050 when over 80% of China's oil demand will be imported.